Analisis Faktor-Faktor Yang Mempengaruhi Komitmen Organisasi Penelitian Pada Karyawan PT. Aseli Dagadu Djokdja - Aknesta Aknesta; Kusuma Chandra Kirana; Didik Subiyanto (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This study aims to examine the effect of work motivation, job satisfaction, work environment, and compensation on organizational commitment. All populations of 50 employees were used as respondents. Data processing was carried out using the SPSS program. To get good and correct analysis results, validity and reliability tests are carried out first. Furthermore, descriptive analysis was carried out for demographic data and descriptions for all research variables. Prior to the analysis to prove the hypothesis, the classical assumption test was first performed. The results of this study prove that work motivation has a significant effect on organizational commitment. Job Satisfaction has a significant influence on organizational commitment. The work environment significantly influences organizational commitment. Organizational commitment is also significantly influenced by compensation. From the results of this empirical research, it strengthens logical thinking, which will have implications for managerial decision making at PT. Aseli Dagadu Djokdja